Sports nature culture. A participatory approach to reconstruct a multidimensional cultural landscape by leveraging outdoor sports - Camocini, Barbara; Daglio, Laura; Podda, Roberto (Frontiers in Sports and Active Living, 2025)
The growing popularity of outdoor sports in natural landscapes is reshaping sport tourism, particularly in rural and mountainous areas, offering opportunities for sustainable development but also presenting risks to the environmental and cultural heritage. This study focuses on Oliena, a village in Sardinia (Italy) that is undergoing depopulation and economic decline, leveraging participatory approaches through Nature Sports to strengthen the community identity and the bond with its landscape. Since 2016, the team of researchers have conducted participatory design workshops and field activities, including creative installations, and multidimensional narrative of the urban and landscape heritage leveraged by Oliena's unique cultural and natural resources. Data collection involved stakeholder meetings, interviews, and sports experiences, fostering a shared understanding of the interplay between the community and its environment. This experience led to the establishment of a Permanent Workshop for continuous engagement and community capacity building. The integrated approach experienced in the case study of Oliena showcases how participatory approaches and shared sports experiences can reconnect communities with their heritage, promoting tourism that is both enriching and sustainable. It highlights how Nature Sports, integrated within cultural landscapes, can provide a transformative framework for sustainable tourism, offering a methodology with scalable insights for other regions.